Obtenção do extrato de própolis assistida por micro-ondas, aplicação em linguiça toscana e avaliação da sua capacidade antioxidante - Viera, Vanessa Bordin (2012)
The present study aimed to evaluate the propolis ethanolic extract obtained by microwave assisted extraction regarding to its phenolic compounds amount, antioxidant activity and its use in the Tuscany Italian sausage. The amount of total phenolic content and antioxidant activity was evaluated by the DPPH method. After optimization, the selected extraction parameters were used to obtain extracts used in 0, 5%, 1% and 2% (p/v) concentrations in the Tuscan Italian sausage manufacture, wich were analyzed during 56 days. It was analyzed humidity, protein, ash and fat. The sausages were analyzed every seven days for pH, color, TBARS index and microbiological analyses. The sensory analysis was evaluated through the acceptability test with 9 points in the Hedonic Scale and the acceptability index was calculated. The results obtained for centesimal composition are in accordance to the Brazilian law. Regarding color, the product presented a yellowish color, that is, a lighter one. In the final storage period the TBARS value for the sausage with 2% extract was 0,249±0,021 and the control one was 1,641±0,037 MDA/Kg de amostra. The values for Staphylococcus positive coagulase; Salmonella; Total Coliforms and fecal Coliforms were lower than the values limited by law. The acceptability index (IA %) for taste and smell of the products with the highest concentration of propolis was not satisfactory, being lower than 70%. For 0,5% and 1% concentrations the acceptability indexes for color, smell, taste, texture and general appearance were satisfactory, higher than 70%. It is possible to conclude that the extraction with microwaves is efficient and the addition of 0,5%, 1% and 2% propolis extract can be used in the Tuscan Italian sausage manufacture to make its shelf life longer facing the lipid oxidation.